Study on the Mechanism of Experiment Change and Interharmonic Frequency Doubling Error of Rolling Bearing Fault Characteristic Frequency - Sun Xianbin; Tan Jiwen; Wen Yan (Jixie chuandong)
The calculation of characteristic frequency of rolling bearing fault is the important theory basis for rolling bearing fault diagnosis and condition monitoring all the time. Through the experiments,discovering that the experimental results are fail to agree with the theoretical calculation value,the experimental data is not repeatable,the characteristic frequencies aren’t diploid related to each other,that is exist with the interharmonic frequency doubling error,and so on. Then,the root cause of errors of experiment results change characteristic frequency and interharmonic frequency doubling are analyzed and the methods of improving errors theoretically are discussed under the above basic study,a theoretical basis for rolling bearing fault diagnosis and improving method is provided.